PATH57 Altered structural and functional network connectivity predicts cognitive function after traumatic brain injury. Issue 11 (22nd October 2010) - Sharp, D; Leech R, Powell J; Bonnelle, V; Beckmann, C F; De Boissezon, X; Greenwood, R; Kinnunen, K
Abstract : Traumatic brain injury (TBI) often results in cognitive impairments that limit recovery. The key pathophysiological predictors of recovery are uncertain, but the disruption of brain networks by diffuse axonal injury (DAI) is likely to be important. Here we use MRI to investigate the effect of TBI on structural and functional connections within cognitive brain networks. We studied 21 patients after TBI, 10 with microbleed evidence of DAI visible on MR. Diffusion tensor imaging (DTI) was used to quantify white matter disruption and functional MRI (fMRI) to study network function. Subjects were studied at "rest" and during performance of a simple task that assessed speed of processing information speed, which is often impaired after TBI. Compared to age-matched controls, TBI patients showed slow speeds of information processing and widespread white matter disruption (Abstract PATH57 Figure 1A ). We expected this structural damage to impact brain network function. Patients with more severe white matter damage within core tracts showed greater disruption of the default mode network (DMN), a functional brain network implicated in cognitive control (Abstract PATH57 Figure 1B and C ). In addition, DMN integration both predicted information processing speed and also patterns of brain activation associated with task performance. Taken together our results demonstrate how changes in the structural connectivity impact the function of distributed brain networks after TBI, and how this relates to behaviour.